Pengaruh Fungsi Perencanaan, Pelaksanaan dan Evaluasi Terhadap Mutu Pembelajaran Pada SDN Batu Tambung di Makassar - Muhtazib Muhtazib; Mardiana Ibrahim (Transformasi: Journal of Economics and Business Management, 2022)
This research aims to determine the influence of the Planning, Implementation and Evaluation variables on the quality of learning at the Batu Tambung State Elementary School in Makassar, South Sulawesi Province. To find out what variables have the most significant influence on the quality of learning quality at the Batu Tambung State Elementary School in Makassar, South Sulawesi Province. This research uses qualitative and quantitative research methods. The results of the research show that the three independent variables, namely learning design, learning implementation and learning evaluation simultaneously have a positive and significant effect on the quality of learning at the Batu Tambung State Elementary School in Makassar. Factors (variables) in the implementation of learning are those that dominantly influence the quality of learning at the Batu Tambung State Elementary School in Makassar, South Sulawesi Province